AFFAODV: Accept, Filter and Forwarding Multiple RREPs Technique on AODV to Prevent Blackhole Attacks in MANET - Rama Rao Tandu, Dr. P.V. Nageswara Rao (International Journal of Advanced Science and Technology, 2020)
The AODV is an extension of the DSDV and DSR routing Protocol. The malicious nodes in black hole attack use AODV's behavior and reveal its malicious behavior when transmitting data means that don’t forward data packets. So the PDR and Throughput is notably reduced.  Moreover, the retransmission mechanism produces heavy traffic. To keep away from this missing data packets, the researchers have carried out many detection approaches.  But completely not prevented, so this paper suggested a new technique i.e called “Accept, Filter and Forwarding Multiple RREPs Technique” to stop Blackhole attacks in MANET and show its results in (NS2).Keywords: - MANET, AODV, Black hole attacks